2002
DOI: 10.1159/000069814
|View full text |Cite
|
Sign up to set email alerts
|

Human chromosome 3: integration of 60 <i>Not</i>I clones into a physical and gene map

Abstract: Sequence tagged sites generated for 60 NotI clones (NotI-STSs) from human chromosome 3-specific NotI-jumping and NotI-linking libraries were physically located using PCR screening of a radiation hybrid (RH) GeneBridge4 panel. The NotI map of chromosome 3 was generated using these RH-mapping data and those obtained earlier by FISH and sequencing of the corresponding NotI clones. The sequences of the NotI clones showed significant homologies with known genes and/or ESTs for 58 NotI-STSs (97%). These 58 NotI clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
5

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
1
8
0
5
Order By: Relevance
“…Alternatively, presence of putative WDR1 pseudogenes and a Vrk2 homolog could be supposed on HSA3q21 → q23. A similar observation was reported for three NotI clones from HSA3p21, which were shown to have homology to three different genes located on HSA12 (Sulimova et al, 2002).…”
Section: Orthologysupporting
confidence: 84%
See 3 more Smart Citations
“…Alternatively, presence of putative WDR1 pseudogenes and a Vrk2 homolog could be supposed on HSA3q21 → q23. A similar observation was reported for three NotI clones from HSA3p21, which were shown to have homology to three different genes located on HSA12 (Sulimova et al, 2002).…”
Section: Orthologysupporting
confidence: 84%
“…It was experimentally confirmed that there is a certain statistical connection between CpG islands, NotI sites and expressed sequences in the human genome (Zabarovsky et al, 2000). The contigs of NotI clones were created for HSA3p21 → p14 and HSA3q13 → q23 by means of FISH and RH mapping (Kashuba et al, 1999;Sulimova et al, 2002). Maximal densities of NotI clones within the contigs were shown in T-bands on HSA3p15, HSA3p21.3, HSA3q21 and HSA3q29 (Protopopov et al, 1996).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…By means of RT-PCR experiments using primers located within genomic sequence or across splice sites (AP43R, Sulimova et al, 2002; and pyruvate dehydrogenase beta PDHB, primer sequence in Table 1), all cDNA samples were tested and found to be free of genomic DNA (data not shown).…”
Section: Expression Studiesmentioning
confidence: 99%